Transcriptomic and Proteomic Profiling Reveal the Key Role of AcMYB16 in the Response of Pseudomonas syringae pv. actinidiae in Kiwifruit - Wang, Xiaojie; Li, Yawei; Liu, Yuanyuan; Zhang, Dongle; Ni, Min; Jia, Bing; Heng, Wei; Fang, Zemin; Zhu, Li-wu; Liu, Pu (Frontiers in Plant Science, 2021)
Kiwifruit bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa), is an important disease of kiwifruit (Actinidia Lind.). Plant hormones may induce various secondary metabolites to resist pathogens via modulation of hormone-responsive transcription factors (TFs), as reported in past studies. In this study, we showed that JA accumulated in the susceptible cultivar A. c. var. chinensis ‘Hongyang’ but decreased in the resistant cultivar of A. c. var. deliciosa ‘Jinkui’ in response to Psa. Integrated transcriptomic and proteomic analyses were carried out using the resistant cultivar ‘Jinkui’. A total of 5045 differentially expressed genes (DEGs) and 1681 differentially expressed proteins (DEPs) were identified after Psa infection. Two pathways, ‘plant hormone signal transduction’ and ‘phenylpropanoid biosynthesis’, were activated at the protein and transcript levels. In addition, a total of 27 R2R3-MYB transcription factors (TFs) were involved in the response to Psa of ‘Jinkui’, including the R2R3-MYB TF subgroup 4 gene AcMYB16, which was downregulated in ‘Jinkui’ but upregulated in ‘Hongyang’. The promoter region of AcMYB16 has a MeJA responsiveness cis-acting regulatory element (CRE). Transient expression of the AcMYB16 gene in the leaves of ‘Jinkui’ induced Psa infection. Together, these data suggest that AcMYB16 acts as a repressor to regulate the response of kiwifruit to Psa infection. Our work will help to unravel the processes of kiwifruit resistance to pathogens and will facilitate the development of varieties with resistance against bacterial pathogens.